Training and Assistance of Business Development Strategy Based on Local Wisdom Dokdak Village Community - Suryana, Aan; Darna, Nana; Pajriah, Sri (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
Due to the covid-19 pandemic, the production of blacksmith craftsmen in the Dokdak Village has decreased. This decline occurred due to the weakness of the marketing system and the lack of public knowledge about the values of local wisdom. To empower local wisdom, especially the production of blacksmiths, community service was carried out with the aim of creating a modern marketing system and increasing public understanding. In achieving this goal, the P3 (Planning, Training, and Assistance) method was carried out, in three stages. The first stage of planning begins with a Focus Group Discussion (FGD). The second stage of implementation was a survey of the community around the service locus, by meeting local community leaders. The third stage is mentoring activities on strengthening local wisdom values. The locus of service was carried out in Dokdak Village, Baregbeg Village, Baregbeg District, Ciamis Regency. Participants in the dedication activity consisted of 30 blacksmiths. The results of the training and mentoring evaluation showed that the response of the training participants regarding historical and cultural understanding increased from 42.3% to 84.6%. Then the understanding of the importance of local wisdom values also increased from 34.6% to 76.9%. Furthermore, participants had knowledge related to how to establish business partners, one of which was with local BUMDES (Village Owned Enterprises). The results of online marketing training and assistance had been successfully carried out, namely by registering a blacksmith business group in the Shopee marketplace. This training and mentoring activity was expected to be useful for participants in the Dokdak Village environment, especially in improving welfare/the economy.